2014
DOI: 10.3109/15569527.2014.950379
|View full text |Cite
|
Sign up to set email alerts
|

CPT, the main test method of skin neuronal sensitivity

Abstract: Different degrees of skin susceptibility can be reflected by BT. CPT can be useful for the quantitative evaluation of skin neuronal sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 9 publications
2
9
0
Order By: Relevance
“…The positive-group had lower CPT value than the negative-group at 5 and 250 Hz. The results were consistent with previous studies (6,20,25). And after the CAT, there was significant increase in the CPT value at 5 and 250 Hz which was mediated by unmyelinated C fibre and small A delta fibre.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The positive-group had lower CPT value than the negative-group at 5 and 250 Hz. The results were consistent with previous studies (6,20,25). And after the CAT, there was significant increase in the CPT value at 5 and 250 Hz which was mediated by unmyelinated C fibre and small A delta fibre.…”
Section: Discussionsupporting
confidence: 94%
“…Here, we focus on its characteristic of heighted neural and vascular reaction. Previous studies found that CPT was negatively correlated with TEWL (20,21). The impaired barrier function of skin may cause the exposure of immune system cells and sensitive nerves, leading to discomfort response to otherwise harmless stimuli (22).…”
Section: Discussionmentioning
confidence: 99%
“…Since damage to small cutaneous Aδ and C nerve fibres, especially unmyelinated C-fibres (6), has been described in sensitive skin (5), we expected a significant decrease in the CPT at 5 Hz in sensitive skin compared with non-sensitive skin. This has been described in several studies (13,25,27,28). In some reports, CPT was also reduced at 250 Hz (13,27,28).…”
Section: Discussionsupporting
confidence: 71%
“…These subjects may display normal barrier, which could result in LAST negative. It has also been postulated that DMSO is suitable for assessing cutaneous vascular reactions , whereas LAST is more sensitive to assess cutaneous neurosensivity . Additionally, some subjects with sensitive skin display positive response only to either capsaicin or lactic acid .…”
Section: Discussionmentioning
confidence: 99%